Handbook on international political economy - Pettman, Ralph (World Scientific, 2012)
International political economy (IPE) is a highly complex discipline, drawing not only from the fields of politics and economics, but also those as varied as philosophy, history and anthropology. Now widely accepted as a key dimension to contemporary world affairs, it is no longer possible to talk about international relations without talking about production and distribution, finance and investment, as well as consumption and trade. To ensure that our understanding of these topics is relevant to today's world, there is a constant need to revisit and challenge what is known about these topics. Besides being a comprehensive account of international political economy for academic study, this extensive collection also highlights salient issues that scholars, analysts and state leaders are most concerned with in today's world. Amongst these are issues concerning the rise of China and India as new economic superpowers, stability in the EU's political economy, the viability of the existing multilateral system of global trade, recent financial crises, as well as the impact of globalisation and marketisation on the world's workers and our physical environment. With contributions from prominent academics such as Susan K Sell (George Washington University, D.C.) and Geoffrey Blainey (Professor Emeritus, University of Melbourne), this volume makes for both a stimulating and thought-provoking read.